LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI UNTUK MENINGKATKAN KEMATANGAN KARIER SISWA KELAS XII MENGGUNAKAN MEDIA GOOGLE MEET - Dini Istiqomah; Asep Samsudin; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to determine the implementation of group guidance services with discussion techniques to increase career maturity using google meet media, to find out the responses of teachers and class XII students to group guidance services, discussion techniques using google meet media, to find out the obstacles faced by teachers and students when implementing services. group guidance with discussion techniques using google meet media. The research method used is qualitative method. The sample in this study was 4 students from class XII at SMAN 6 Garut. The data of this study were obtained from the results of observations, documentation, and interviews with BK teachers and students on group guidance services with discussion techniques using google meet media. The results showed that the implementation of group guidance services with discussion techniques using google meet media was carried out well. The responses of teachers and students to group guidance services with discussion techniques using google meet media got good results. Obstacles faced by teachers and students in group guidance services with discussion techniques are the absence of quota subsidies from schools and students are sometimes constrained by an inadequate network, BK teachers are also still adjusting to learning using media. So that the delivery of the material that is conveyed is not optimal and students do not understand what the teacher is saying.Keywords: Career Maturity, Group Guidance Services, Discussion Techniques.